Rodinný dům v Hrabové - Pěničková, Klára (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Tato bakalářská práce se zabývá návrhem novostavby rodinného domu na úrovni dokumentace pro provádění stavby. Objekt je tvořen jedním nadzemním podlažím a suterénem. Je navržen pro čtyřčlennou rodinu. Objekt se nachází na svažitém pozemku v obci Hrabová u Dubicka. Základové konstrukce jsou řešeny základovými pasy z prostého betonu. Svislé konstrukce jsou navrženy z betonových tvárnic ztraceného bednění a tvárnic LIAPOR. Stropní konstrukce jsou řešeny jako železobetonové desky. Objekt je zastřešen plochou střechou. Projektová dokumentace je zpracována v počítačovém programu ArchiCAD.

This bachelor´s thesis presents the design of a new house focussing on the project documentation for the building realization. The house comprised of one storey and a basement is designed for a family of four. The building is located in a slope terrain in the village Hrabová u Dubicka. Foundation structures are realized with plain concrete continuous footing. Vertical supportive constructions are designed from lost formwork concrete panels and the Liapor blocks. Ceiling constructions are realized with supported reinforced concrete slabs. The building is flat roof. The project documentation is processed with the help of the ArchCAD computer programme.
Detached family house, Hrabová
Keywords: Rodinný dům; samostatně stojící; svažitý pozemek; podsklepený; plochá střecha; konzola; kontaktní zateplovací systém; obec Hrabová u Dubicka.; Family house; detached house; slope terrain; house with a cellar; flat roof; cantilever; contact thermal insulation system; the village Hrabová u Dubicka.